Análisis constitucional de la suspensión o renuncia de cargos electos derivadas de procedimientos penales en curso - Bértolo Suárez, Iván Gabriel (My University, 2022)
La renuncia o cese en el cargo público derivada de un procedimiento penal en curso ha sido objeto en los últimos años de enfrentamientos políticos desde los partidos. Algunos, han incluido códigos de conducta que prohíben o cesan de inmediato a aquellos diputados, senadores, alcaldes o concejales desde el momento en que se les imputa o investiga por delitos que tienen que ver directamente con su actividad pública. Otros, los mantienen al margen amparados en la presunción de inocencia e independencia judicial, alegando que hasta que no exista sentencia firme no se pronunciarán al respecto. Sin duda, entran en juego aspectos más de responsabilidad social y éticos que puramente jurídicos, pues no existe un respaldo normativo claro y concreto, dejando en manos de la labor interpretativa jurisdiccional la decisión final de cuándo procede cesar en el cargo público ante un procedimiento penal en curso. En la práctica, los partidos políticos suelen optan por “apartar” o dejar en un segundo plano al investigado mientras se resuelve el juicio, para así no tener que tomar una decisión en falso que pueda contravenir sus propios intereses.

The resignation or dismissal from public office as a result of ongoing criminal proceedings has been the subject of political confrontations between parties in recent years. These parties have included codes of conduct that prohibit or immediately dismiss deputies, senators, mayors or councillors from the moment they are charged with or investigated for crimes directly related to their public activity. They keep them on the sidelines under the presumption of innocence and judicial independence, claiming that until there is a final judgement they will not rule on the matter. The resignation or dismissal from public office as a result of ongoing criminal proceedings has been the subject of political confrontations between parties in recent years. Some parties have included codes of conduct that prohibit or immediately dismiss deputies, senators, mayors or councillors from the moment they are charged with or investigated for crimes directly related to their public activity. Others keep them on the sidelines on the grounds of the presumption of innocence and judicial independence, claiming that they will not rule on the matter until there is a final judgement. Undoubtedly, aspects of social and ethical responsibility rather than purely legal ones come into play, as there is no clear and concrete regulatory support, leaving the final decision on when it is appropriate to resign from public office in the face of ongoing criminal proceedings to the interpretative work of the courts. In practice, political parties often choose to 'set aside' or put the person under investigation on the back burner pending trial, so as not to have to make a false decision that might contravene their own interests.
Grado en Análisis de Negocios/Business Analytics y Grado en Derecho
Keywords: 56 Ciencias Jurídicas y Derecho; 5605 Legislación y leyes nacionales; 560504 Derecho constitucional; KDG